Faithful translation in novel ‘City of Fallen Angels’ - Fahrunnisa Haerani (LADU: Journal of Languages and Education, 2023)
Background:  Many young people now are starting to like reading novels. On this occasion, this research will discuss the translation of novels from English to Indonesian. Novel is a long prose narrative that deals with human life. In this research, the authors focus on faithful translation found in English novels and translated into indonesian. Focused on analyzing how faithful translation is applied by translators in translating novels using Newmark's theory. Purpose: This research aims to determine faithful translation in the novel City of Fallen Angels In the English-Indonesia Version. Design and methods: The method of this research was a descriptive method, using a quantitative approach. The researcher read the novel in both English and Indonesian as part of the data collection process, and then examined the faithful translation. Results: The results obtained from this research indicate that there are thirty data which are of the faithful translation type. Faithful translation based on these findings it can be concluded that translators maintain grammatical and lexical degrees when translating cultural terms. The translator tries to communicate in the target language according to the story events that occur. The faithful translation method emphasizes the source language, it means trying to produce the contextual meaning of the source language but still with the grammatical structure of the target text.